Robotic subxiphoid-optical thymectomy. (21st April 2022) - Shimomura, Masanori; Ishihara, Shunta; Okada, Satoru; Inoue, Masayoshi
Abstract: Robot-assisted thymectomy through a subxiphoid scopic approach can provide a good surgical view, similar to that of median sternotomy. We originally used the subxiphoid port only for the robotic scope to avoid instrument collision with the assistant device. This approach, robotic subxiphoid-optical thymectomy, is advantageous for the safe and accurate dissection of the bilateral phrenic nerves and the left brachiocephalic vein, which are especially needed in extended thymectomy for patients with myasthenia gravis. Abstract : Robotic thymectomy for thymic tumour and myasthenia gravis (MG) show good perioperative results and low local recurrence with med-term outcomes [1].